CHOICE OF A STRATEGIC DETERRENCE MODEL OF REPUBLIC OF SERBIA - Forca, Bozidar (ACADEMIC REVIEW, 2025)
Strategic deterrence implies the ways in which the state (coalition) avoids war, that is, tries to deter a potential opponent from aggressive intentions. The aim of this research is to analyze the model of strategic deterrence that the Republic of Serbia is opting for.The research has a theoretical and empirical character. Scientific methods were primarily used in the research: comparative; case study and content analysis.. In general, the results of the research are: 1) The basic models of strategic deterrence, from a historical point of view, are the strengthening of military power and neutrality; 2) the basic ways of strengthening military power are expressed through one’s own power, including nuclear weapons and the creation of military alliances, when it comes to world powers and bandwagoning, when it comes to small and underdeveloped states; 3) the former permanent neutrality, in modern conditions, has been transformed into military neutrality and 4) the Republic of Serbia has been applying military neutrality and strengthening military power since gaining independence in 2006, with the official position that it will not join military alliances, especially not in NATO. The conclusion of the work can be as follows: The basic model of strategic deterrence of the Republic of Serbia should be military neutrality, and the strengthening of its military power should be harmonized with the balance of threats.